2023
DOI: 10.55489/njcm.140420232800
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of COVID-19 Lockdown on Parents Handling Children with Disability in Chennai, India

Abstract: Introduction: Millions around the globe were directly or indirectly affected by COVID-19 pandemic. The COVID-19 epidemic has harmed the lives of children with special needs in many ways, whether directly or indirectly. Few studies have evaluated the Impact of covid-19 lockdown among children with disability. However, the Impact of COVID on parents dealing with special children was scarcely studied in detail. Investigating parental stress, worries, and morbidity during the lockdown is particularly important for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Parents with any recent trauma, mental disorders, or major diseases and undergoing treatment for themselves were excluded. After obtaining ethics approval, a semi-structured questionnaire was used to assess the Impact of the covid-19 lockdown [32]. Collected data were analyzed using SPSS v.21.…”
Section: Case Study 2: the Impact Of Covid-19 Lockdown On Parents Han...mentioning
confidence: 99%
See 1 more Smart Citation
“…Parents with any recent trauma, mental disorders, or major diseases and undergoing treatment for themselves were excluded. After obtaining ethics approval, a semi-structured questionnaire was used to assess the Impact of the covid-19 lockdown [32]. Collected data were analyzed using SPSS v.21.…”
Section: Case Study 2: the Impact Of Covid-19 Lockdown On Parents Han...mentioning
confidence: 99%
“…The study concluded that COVID-19 outbreak and lockdown significantly impacted the parents of disabled children. It is high time we give importance to these parents of children with special needs during this pandemic to help them during similar occasions in the future [32].…”
Section: Case Study 2: the Impact Of Covid-19 Lockdown On Parents Han...mentioning
confidence: 99%